Learning from Peptides to Access Functional Precision Polymer Sequences - Maron, Eva; Swisher, Jordan H.; Haven, Joris J.; Meyer, Tara Y.; Junkers, Tanja; Börner, Hans G. (Angewandte Chemie International Edition, 2019)
Functional precision polymers based on monodisperse oligo(N‐substituted acrylamide)s and oligo(2‐substituted‐α‐hydroxy acid)s have been synthesized. The discrete sequences originate from a direct translation of side‐chain functionality sequences of a peptide with well‐studied properties. The peptide was previously selected to solubilize the photosensitizer meta‐tetra(hydroxyphenyl)chlorin. The resulting peptidomimetic formulation additives preserve the drug solubilization and release characteristics of the parent peptide. In some cases, superior properties are obtained, reaching up to 40 % higher payloads and 27‐times faster initial drug release. Not lost in translation: A new strategy to guide sequence design for accessing functional precision polymers is described. The direct translation of side‐chain functionality sequences into nonpeptidic backbones leads to macromolecules that mimic or improve on the properties of the parent peptide. As an example, the approach was applied to a peptide‐based formulation additive to solubilize a photosensitizer drug.